Convective Transfer Analysis of Magnetised Ternary Hybrid Nanofluid over a Linear Stretching Sheet: Non-Similar Solutions - Jan, Ahmed; Aslam, Farida; Adnan, Rubina (Archives of Thermodynamics, 2026)
Use of nanofluids to improve heat transfer properties has drawn considerable concern due to their wide use in various applications such as electronic appliances, fuel cell batteries and hybrid-powered engines. These are only a few examples of the many applications of heat transfer that can greatly utilise the distinctive properties of nanofluids. A magnetohydrodynamic nanofluid convective study is carried out for a sheet stretched under a non-uniform heat source/sink in a permeable medium. The heat transfer analysis simulations entail dissipation of porosity and the presence of Ohmic heating. Non-similarity transformations are then applied to the equations that have been formulated to derive dimensionless partial differential equations. Local non-similarity approach has been used to transform partial differential equations into an equation where partial differential equations can be solved as ordinary differential equations, using the bvp4c MATLAB tool. Every physical parameter is represented in a graphical representation. Moreover, the tables that present the summary of the skin friction coefficient and Nusselt number are evaluated in detail. The main findings of this study include the fact that an increase in the strength of the magnetic field decreases the fluid velocity but improves the thermal distribution. It has been observed that the higher the porosity, the lower the skin friction. In addition, high radiation levels also help in having a more favourable temperature field.